Li-Fi – the future of wireless technology - Shyamala Kumari, C; Florence, S; Prema, K; Leema Priyadharshini, L (International Journal of Engineering and Technology, 2018)
In this era of technology the number of gadgets such as mobilephones, smartwatches, digital glasses and health trackers are used extensively by people in a large scale. The data traffic is abundant as the available radio frequency is limited, so the demand for the wireless network is keep on increasing. In order to meet the future demands there was a development in the optical communication method known as Li-Fi(Light-Fidelity).This will offer more bandwidth than the RF spectrum. They make use of LEDs to transmit the data. The main advantages of the Li-Fi is that there is no need of licensing and has a huge amount of unregulated bandwidth and there is zero electromagnetic interference so that the health hazards are nullified.